Lycopene: A Critical Review of Digestion, Absorption, Metabolism, and Excretion - Joseph Arballo; Jaume Amengual; John W. Erdman (MDPI AG, 2021)
Lycopene is a non-provitamin A carotenoid that exhibits several health benefits. Epidemiological data support a correlation between lycopene intake and the attenuation of several chronic diseases, including certain types of cancers and cardiovascular diseases. It is currently unknown whether the beneficial effects are from the native structure of lycopene or its metabolic derivatives: lycopenals, lycopenols, and lycopenoic acids. This literature review focuses on the current research on lycopene digestion, absorption, metabolism, and excretion. This review primarily focuses on in vivo studies because of the labile nature and difficulty of studying carotenoids within in vitro experimental models. The studies presented address tissue accumulation of lycopene, the modification of bioavailability due to genetic and dietary factors, and lycopene cleavage by the enzymes ß-carotene oxygenase 1 (BCO1) and ß-carotene oxygenase 2 (BCO2). The current literature suggests that the majority of lycopene is cleaved eccentrically by BCO2, yet further research is needed to probe the enzymatic cleavage activity at the tissue level. Additionally, results indicate that single nucleotide polymorphisms and dietary fat influence lycopene absorption and thus modify its health effects. Further research exploring the metabolism of lycopene, the mechanisms related to its health benefits, and optimal diet composition to increase the bioavailability is required.